Combined Aerobic and Resistance Exercises Evokes Longer Reductions on Ambulatory Blood Pressure in Resistant Hypertension: A Randomized Crossover Trial - Nayara Fraccari Pires; Helio José Coelho-Júnior; Bruno Bavaresco Gambassi; Ana Paula Cabral de Faria; Alessandra Mileni Versuti Ritter; Catarina de Andrade Barboza; Silvia Elaine Ferreira-Melo; Bruno Rodrigues; Heitor Moreno Júnior (Cardiovascular Therapeutics)
Aim. The present study compared the acute effects of aerobic (AER), resistance (RES), and combined (COM) exercises on blood pressure (BP) levels in people with resistant hypertension (RH) and nonresistant hypertension (NON-RH). Methods. Twenty patients (10 RH and 10 NON-RH) were recruited and randomly performed three exercise sessions and a control session. Ambulatory BP was monitored over 24 hours after each experimental session. Results. Significant reductions on ambulatory BP were found in people with RH after AER, RES, and COM sessions. Notably, ambulatory BP was reduced during awake-time and night-time periods after COM. On the other hand, the effects of AER were more prominent during awake periods, while RES caused greater reductions during the night-time period. In NON-RH, only RES acutely reduced systolic BP, while diastolic BP was reduced after all exercise sessions. However, the longest postexercise ambulatory hypotension was observed after AER (~11 h) in comparison to RES (~8 h) and COM (~4 h) exercises. Conclusion. Findings of the present study indicate that AER, RES, and COM exercises elicit systolic and diastolic postexercise ambulatory hypotension in RH patients. Notably, longer hypotension periods were observed after COM exercise. In addition, NON-RH and RH people showed different changes on BP after exercise sessions, suggesting that postexercise hypotension is influenced by the pathophysiological bases of hypertension.